1998
DOI: 10.1021/ja9809206
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Oxidation oftert-Butyl Disulfide. Synthesis oftert-Butanesulfinamides,tert-Butyl Sulfoxides, andtert-Butanesulfinimines

Abstract: The first example of the catalytic asymmetric oxidation of tert-butyl disulfide (1) is described. The product, tert-butyl tert-butanethiosulfinate (2) is obtained with 91% enantiomeric excess in yields of ≥92% on scales as large as 1 mol. The application of H2O2 as stoichiometric oxidant in the presence of 0.25 mol % of VO(acac)2 and 0.26 mol % of a chiral Schiff base ligand, 6a, is both convenient and cost-effective. Thiosulfinate ester 2 is chemically and optically stable and serves as an excellent precursor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
217
0
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 365 publications
(221 citation statements)
references
References 56 publications
(57 reference statements)
3
217
0
1
Order By: Relevance
“…Commercial grade solvents were dried and purified by standard literature procedures. The 1 H NMR (300 MHz) and 13 C NMR (75 MHz) spectra were recorded on a Brucker-300 spectrometer. Optical rotation data were recorded on a Perkin-Elmer Polarimeter-341.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercial grade solvents were dried and purified by standard literature procedures. The 1 H NMR (300 MHz) and 13 C NMR (75 MHz) spectra were recorded on a Brucker-300 spectrometer. Optical rotation data were recorded on a Perkin-Elmer Polarimeter-341.…”
Section: Methodsmentioning
confidence: 99%
“…The residue was purified by column chromatography with petroleum ether/EtOAc (4:1, V/V) to afford 7. 13 Under an argon atmosphere, to a solution of 7 (1.0 mmol) in THF (5 mL) was added dropwise either n-BuLi (0.5 mL, 1.25 mmol, 2.5 M solution in hexane) or LDA (1.1 mmol) at À78°C, and the mixture was stirred for 1 h at À50°C. Under an argon flow, elemental sulfur (S 8 ) (64 mg, 2.0 mmol) was added to the reaction mixture at À78°C, and the temperature was allowed to slowly warm to room temperature.…”
Section: Typical Procedures For Synthesis Of Ligands 4d-kmentioning
confidence: 99%
“…The know chiral sulfinamides, (R)-12, (S)-12 and (S)-13, were prepared by the methods of Davis [13] and Ellman [14] or purchased from the Aldrich Chemical Company. These compounds were used to prepare the N-benzoyl and N-tert-butoxycarbonyl (NBoc) derivatives, (R)-14, and (S)-15 respectively, in good yields (83-85%) according to Scheme 3.…”
Section: Resultsmentioning
confidence: 99%
“…69 It was found that when R 1 = t-butyl, optimal results were obtained. Investigations revealed that the substituent at R 2 played no steric role in the oxidation, however the electronic effects of this substituent were important, for example when R 2 = NO 2 or OMe, there was a decrease in the enantioselectivity of the oxidation.…”
Section: Scheme 24mentioning
confidence: 99%
“…Results obtained by Ellman 68,69 and Zhu 99 employing vanadium catalysts in asymmetric oxidation indicated that chloroform was a good solvent for asymmetric sulfide oxidations. Jackson reported that kinetic resolution was enhanced carrying out the reaction in chloroform rather than dichloromethane at 20 o C and kinetic resolution was improved even further by carrying out the reaction in chloroform at 0 o C (Scheme 90).…”
Section: Scheme 89mentioning
confidence: 99%